PEMIKIRAN ANALITIS DAN INOVASI DALAM PENGAJARAN BAHASA ARAB ERA INDUSTRI 4.0 - Afif, Muthoharun (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
This paper aims to describe aspects of analytical thinking and innovation in Industrial 4.0 Arabic language teaching. From the results of the discussion it was concluded: instructors of Arabic should understand mastery: 1) current trends and issues in teaching and learning Arabic, first writing Arabic characters that are properly connected, Qur'anic Arabic is an example for written formal Arabic (hereinafter referred to as as Standard Arabic Language; 2) The social context of the transmission of knowledge, at the same time, the reading session continues the practice of long-established culture. From a psychological perspective on the process of language learning, there may be no useful differences between 'second' and 'foreign' languages. , because it can be said that the acquisition process is identical. However, in the context of education and politics, the status of a language in a particular society is important, and the difference is important; 3) Core Issues in the Practice of Arabic language learning is the work of spending their time, environmental impact, and attitudes or considering reading as insignificant; 4) Communicative Competencies, Language Variations and Using Frames in Arabic Teaching and Learning that 'time spent abroad is one of the most powerful variables' which predicts second language skills; 5) Arabic Language Program, Design and Curriculum goals; What allows translingual to progress in this context is their adaptive disposition. This disposition is greatly aided by their reflective skills, motivated by openness to learning; 6) Content-Based Teaching and Learning Approaches emphasize the need for innovation in pedagogical theories and practices. This explains the current linguistic dilemma and identifies the space for bilingualism and pluriculturalism which diagrams use content, cognition and communication in linguistic culture; 7) The emergence of reliable computing resources, searching for various corporations for certain structures and uses has been made much easier and Arabic linguistic researchers can now process more data than before. Most corporations are in MSA, but Arabic-language corporate development is also ongoing; 8) Arabic Language Screening Tests are based on English tests such as Clinical Evaluation of Language Basics and Word Knowledge Test.